Consciousness and the existence of God : a theistic argument - Moreland, James Porter, 1948- (Routledge studies in the philosophy of religion., 2008)
In Consciousness and the Existence of God, J.P. Moreland argues that the existence of finite, irreducible consciousness (or its regular, law-like correlation with physical states) provides evidence for the existence of God. Moreover, he analyzes and criticizes the top representative of rival approaches to explaining the origin of consciousness, including John Searle's contingent correlation, Timothy O'Connor's emergent necessitation, Colin McGinn's mysterian ''naturalism, '' David Skrbina's panpsychism and Philip Clayton's pluralistic emergentist monism. Moreland concludes that these approaches should be rejected in favor of what he calls ''the Argument from Consciousness.''